2017
DOI: 10.1111/cobi.12918
|View full text |Cite
|
Sign up to set email alerts
|

Restoration planning to guide Aichi targets in a megadiverse country

Abstract: Ecological restoration has become an important strategy to conserve biodiversity and ecosystems services. To restore 15% of degraded ecosystems as stipulated by the Convention on Biological DiversityPalabras Clave: análisis espacial multicriterio, planificación sistemática de la conservación, proceso participativo, sitios clave de biodiversidad, factibilida de restauración

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 59 publications
(69 reference statements)
0
29
0
3
Order By: Relevance
“…Different types of spatially based biodiversity information can and should be incorporated into systematic restoration planning at a range of spatial scales, but there are no tools that provide broadly applicable models, as is the case for ecosystem services. At a national or regional scale, inventory data on the geographic distribution and abundance of species can be used to indicate priority areas for reserves and biological corridors based on criteria such as local species richness, richness of endemic or rare species, refugia for endangered species or assessing species complementarity in protected area networks (Tobón et al 2017). At the landscape scale, biodiversity assessment data can play an integral role in FLR planning, including prioritizing locations and types of biological corridors, assessing species complementarity networks, and evaluating potential outcomes of different restoration interventions on local-and landscape-scale species and functional diversity.…”
Section: Tools For Incorporating Biodiversity Into Systematic Restoramentioning
confidence: 99%
See 4 more Smart Citations
“…Different types of spatially based biodiversity information can and should be incorporated into systematic restoration planning at a range of spatial scales, but there are no tools that provide broadly applicable models, as is the case for ecosystem services. At a national or regional scale, inventory data on the geographic distribution and abundance of species can be used to indicate priority areas for reserves and biological corridors based on criteria such as local species richness, richness of endemic or rare species, refugia for endangered species or assessing species complementarity in protected area networks (Tobón et al 2017). At the landscape scale, biodiversity assessment data can play an integral role in FLR planning, including prioritizing locations and types of biological corridors, assessing species complementarity networks, and evaluating potential outcomes of different restoration interventions on local-and landscape-scale species and functional diversity.…”
Section: Tools For Incorporating Biodiversity Into Systematic Restoramentioning
confidence: 99%
“…Yoshioka et al (2014) identified priority restoration areas in Japan based on past and current distributions of breeding bird species regarded as endangered, the total area targeted for restoration and the feasibility of restoration. Tobón et al (2017) used a six-step approach to prioritize potential sizes for restoration that support national scale biodiversity conservation goals in the megadiverse country of Mexico. Their highly robust analysis was based on species distribution models for over 80% of the described species of Mexican amphibians, reptiles, birds and mammals, distribution models of threatened plant and tree species, plant family occurrence data, and locations of critical vegetation types.…”
Section: Tools For Incorporating Biodiversity Into Systematic Restoramentioning
confidence: 99%
See 3 more Smart Citations